Clinical decision fatigue: a systematic and scoping review with meta-synthesis - Nicola Grignoli; Serena Petrocchi; Peter Schulz; Luca Gabutti; Greta Manoni; Jvan Gianini (Family Medicine and Community Health)
Objective Decision fatigue (DF) can lead to impaired judgement, decreased diagnostic accuracy and increased likelihood of medical errors. Research on DF is scarce, and little is known about its nature in the clinical context. The objective of the present review was to provide a comprehensive framework to understand how the construct of DF in medical settings has been defined and measured. This review aimed to understand DF determinants and consequences and capture motivational factors overlooked in the existing reviews.Design Systematic and scoping review (ScR) with meta-synthesis.Eligibility criteria Empirical and non-empirical papers on clinical DF or related constructs directly impacting clinical decision-making were considered, with doctors of all ages, sexes and nationalities as participants. The Preferred Reporting Item for Systematic Reviews and Meta-analyses scoping review checklist has been applied and checked.Information sources Six databases were systematically searched by two independent researchers according to a predefined set of keywords.Results 43 papers were included, of which 25 were empirical. The quantitative studies outnumber the qualitative ones and primarily involved residents in Europe/UK and North America. Internal medicine and primary care were the most studied disciplines. Only one sequential cross-sectional study measured DF in the medical setting, and all other studies addressed the construct indirectly. A conceptual analysis of clinical DF, including narrative contributions, a thematic analysis of the data extracted and a meta-synthesis, is provided. Clinical DF was investigated mostly by individual risk factors analysed through multiple intertwined determinants involving cognitive, emotional, behavioural, social and ethical aspects. Relevant risks, protective factors and negative outcomes circularly increasing DF are outlined.Conclusions The review gives solid arguments for developing a clear and coherent definition of clinical DF that allows the implementation of preventive targeted intervention.PROSPERO registration number This systematic review was pre-registered in PROSPERO on 8 November 2023 (available online at: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023476190, registration number CRD4202347619).